Developing Macbox Media in Teaching English Grammar for Indonesian Students - Shofiyuddin, Muh; Mansuro, Lukluan; Nichla Choirin Attalina, Syailin; Febrianti, Nissa (JALL (Journal of Applied Linguistics and Literacy), 2024)
This research aims to develop a learning media namely, Macbox. This media is a kind of flashcard built with the appropriate concept of matching box. This research is a Research and Develoment (R&D) research with four steps, 1) Definition, 2) Design, 3) Development, 4) Dissemination. Interview, observation and test were used to obtain the data. The data results show that the macbox media was suitable for use by students. It can be seen from the validation from the material and media experts. Besides, in the media trial, the pretest results the average score in the control class is 48,02. Meanwhile in the experimental class the average value is 48,47. Then in the posttest score the average score in the control class is 62,76. Meanwhile in the experimental class the average value is 75,41. The data show that it increased students’ grammar mastery who taught using macbox media. Thus, it can be concluded that the development of macbox media is very feasible and effective to used in teaching grammar.